Adjuvant Radiotherapy for Synchronous Bilateral Testicular Seminoma: A Case Report and a Review of the Pertinent Literature - Daniel A. Jones; Elizabeth C. Ester; David Leavitt; Robert Sweet; Badrinath Konety; Gautam Jha; L. Chinsoo Cho (Case Reports in Urology)
Few cases of synchronous bilateral stage I seminomas have been reported in the world literature. We present a case of bilateral synchronous testicular seminoma, the current literature on the management of stage I seminoma, and the implications for radiotherapy. A forty-year-old man presented with synchronous bilateral classical seminomas, both stage IA. After undergoing bilateral inguinal orchiectomy, he received adjuvant external beam radiotherapy, with a standard paraaortic field. After 18 months of followup, he remains well, without evidence of recurrence. Bilateral germ cell tumors (BGCTs) are reported consistently at a low rate. Bilateral radical inguinal orchiectomy is standard of care, yet some groups have proposed an organ preservation approach. Of the reported cases of bilateral stage I synchronous GCT, with concordant seminoma histology, most of them were treated with bilateral orchiectomy and adjuvant radiotherapy. Although morbidity associated with radiotherapy directed at the abdomen is not negligible, adjuvant paraaortic radiotherapy remains safe and well-tolerated treatment regime. Bilateral synchronous stage I seminoma of the testes is rare. Organ preservation remains investigational. Chemotherapy is probably a reasonable option. We propose that patients with bilateral stage I synchronous GCT, with concordant seminoma histology, should be managed with bilateral orchiectomy, followed by paraaortic radiotherapy.